2015
DOI: 10.1007/s10549-015-3303-9
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 18F FDG-PET/CT for predicting prognosis of luminal-type breast cancer

Abstract: Postoperative prognosis is better for hormonal receptor-positive breast cancer than for other phenotypes; however, there are no definitive predictive factors for relapse or survival. This study aimed to evaluate the maximum standardized uptake value (SUVmax) on 18F-fluoro-2-deoxy-glucose positron emission tomography/computed tomography (FDG-PET/CT) and clinicopathological characteristics as possible predictors of postoperative relapse-free survival (RFS) and overall survival (OS) in hormonal receptor-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
57
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 32 publications
6
57
1
Order By: Relevance
“…With regard to the biological subtypes, previous studies have described relationships between tumour metabolism and prognosis in hormonal receptor positive and luminal HER2 negative BC [20,21]. In the present study, a separate ROC curve analysis of the three biological categories did not improve the prognostic performance of semiquantitave metabolic values obtained in the global sample, although we observed that HER2 positive and basal tumours displayed higher SUV T with respect to luminal HER2 negative tumours.…”
Section: Discussioncontrasting
confidence: 76%
“…With regard to the biological subtypes, previous studies have described relationships between tumour metabolism and prognosis in hormonal receptor positive and luminal HER2 negative BC [20,21]. In the present study, a separate ROC curve analysis of the three biological categories did not improve the prognostic performance of semiquantitave metabolic values obtained in the global sample, although we observed that HER2 positive and basal tumours displayed higher SUV T with respect to luminal HER2 negative tumours.…”
Section: Discussioncontrasting
confidence: 76%
“…Therefore, this modality is unsuitable for predicting pCR (11,12). Positron emission tomography/computed tomography (PET/CT) is considered useful for diagnosing (13) and assessing the prognosis (14,15) of invasive breast cancer. Although it is also useful for assessing treatment effects (16), the specificity of PET/CT for pCR after chemotherapy is low (17) and the procedure is expensive.…”
mentioning
confidence: 99%
“…In the univariate and multivariate analyses, SUV max was identified as the only significant factor for overall survival (SUV max cutoff value of 6). Patient's age, Clinical T score, clinical N score and nuclear grade were not predictive for overall survival [10].…”
mentioning
confidence: 84%
“…In a recent preliminary report, the same team also suggested that SUV max of 4 to be used as a cutoff value to estimate the Oncotype DX RS (to separate low-tointermediate from high RS) [9]. In the study by Aogi et al [10], 262 stage I-III luminal BC patients (187 with T1 tumour) had 18 FDG-PET/CT before initial therapy. In the univariate and multivariate analyses, SUV max was identified as the only significant factor for overall survival (SUV max cutoff value of 6).…”
mentioning
confidence: 99%
See 1 more Smart Citation